PENGEMBANGAN DESAIN ZONA TAMAN BERMAIN PAUD BAITHANI TENGGER DI DESA TUTUR, NONGKOJAJAR – PASURUAN SEBAGAI KEGIATAN SERVICE LEARNING MATA KULIAH ARSITEKTUR ANAK - Christine Wonoseputro (Institute of Research and Community Outreach - Petra Christian University, 2014)
Service Learning activities has been implemented as Children’s Architecture subject teaching methods, which has been devided into 3 learning steps: theory development, public space exploration, and live in activity at Tutur Village, Nongkojajar Pasuruan as the application of it. In the process of learning, students do not only serve public services to the society, but they try to understand and analyse the real social problem that being faced by the society. Students will learn solving the problem and giving suggestion to them as a statement of partnership in PAUD Baithani Tengger in Tutur Village, Nongkojajar Service Learning activity.